Molecular cloning, manipulation and expression of the laccase gene (IacA) of Pleurotus ostreatus in Saccharomyces cerevisiae - Roth, Robyn Lindsay (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1997.